Why Did Europe Decide to Move to a Single Currency 25 Years Ago? - Niels Thygesen (Intereconomics, 2016)
Many Europeans today ask why the European Community chose the bold strategy of pursuing an Economic and Monetary Union at a time when a number of political and economic issues had not yet been resolved. Many economists like to think that the economic case for EMU was weak and that the decision was taken strictly on political grounds. As someone who had the privilege of being involved in the early preparatory efforts, I would argue that this is a misreading of history. I believe there was both a strong economic case for moving towards a single currency and a rare political opportunity for implementing it around 1990.
Keywords: 330; Währungsumstellung; Eurozone